The burden of interactivity – eroticism and sexuality in computer games - Cielecka, Magdalena (Replay. The Polish Journal of Game Studies, 2014)
Sexuality tends to find its way through all media, video games included. Yet, in-game erotica rarely varies from safe and tamed ways of depicting sexual intercourse typical of other audiovisual media. Something unique for computer games alone is that the productions containing interactive erotic scenes are very scarce. The aim of this paper is to analyse the most common examples of these, in order to produce a common set of scientific problems, which may form the basis for further research.